Salvage Therapy in Acute Severe Ulcerative Colitis: Current Practice and a Look to the Future - Tamir-Degabli, Natalie; Maharshak, Nitsan; Cohen, Nathaniel A. (Turkish Journal of Gastroenterology, 2023)
The risk of urgent bowel resection increases significantly among patients hospitalized with acute severe ulcerative colitis. In-hospital management requires quick diagnostic, therapeutic, and decision-making, combined with a multi-disciplinary approach and accessibility to multiple therapeutic options. However, the optimal strategy is still debatable. We performed a review of the current options for salvage therapy as well as novel therapy options emerging. We reviewed studies reporting outcomes of hospitalized steroid-refractory acute severe ulcerative colitis treated with salvage therapy (calcineurin inhibitors, infliximab) as well as studies using novel biologic, small molecules, antibiotics, and artificial intelligence to optimize therapy. We collected statistical data about patient factors that impact clinical management and how these can be applied to the real-life practice in order to prescribe a more personalized medicine. Several new drugs and approaches have shown benefits during the last decades for the management of acute severe ulcerative colitis. This effort is driven by the necessity of more effective, safe, and rapidly active therapeutic options with better convenient routes of administration, in order to improve therapeutic outcomes and quality of life for patients. The next step will be tailored medicine according to patients’ profiles, taking into account disease characteristics, laboratory parameters, and patients’ preferences. Cite this article as: Tamir-Degabli N, Maharshak N, Cohen NA. Salvage therapy in acute severe ulcerative colitis: Current practice and a look to the future. Turk J Gastroenterol. 2023;34(6):576-583.